Explanation:
Simplifying 40 = 15 + -9x + -2
Reorder the terms: 40 = 15 + -2 + -9x
Combine like terms: 15 + -2 = 13 40 = 13 + -9x
Solving 40 = 13 + -9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9x' to each side of the equation. 40 + 9x = 13 + -9x + 9x
Combine like terms: -9x + 9x = 0 40 + 9x = 13 + 0 40 + 9x = 13
Add '-40' to each side of the equation. 40 + -40 + 9x = 13 + -40
Combine like terms: 40 + -40 = 0 0 + 9x = 13 + -40 9x = 13 + -40
Combine like terms: 13 + -40 = -27 9x = -27
Divide each side by '9'. x = -3
Simplifying x = -3